Estimating Quantile Regressions with Multiple Fixed Effects through Method of Moments - Fernando Rios-Avila; Leonardo Siles; Gustavo J. Canavire Bacarreza (Institute of Labor Economics (IZA), 2024)
This paper proposes a new method to estimate quantile regressions with multiple fixed effects. The method, which expands on the strategy proposed by Machado and Santos Silva (2019), allows for the inclusion of multiple fixed effects and provides various alternatives for estimating standard errors. We provide Monte Carlo simulations to show the finite sample properties of the proposed method in the presence of two sets of fixed effects. Finally, we apply the proposed method to two different examples using macroeconomic and microeconomic data and allowing for multiple fixed effects with robust results.
Keywords: C21; C22; C23; 330; fixed effects; linear heteroskedasticity; location-scale model